1994
DOI: 10.1002/gepi.1370110106
|View full text |Cite
|
Sign up to set email alerts
|

Sibling correlations and segregation analysis of age‐related maculopathy: The beaver dam eye study

Abstract: Sibling correlations were evaluated and segregation analysis was performed on age-dependent maculopathy scores of the right and left eyes of individuals from 564 families in the Beaver Dam Eye study. There is evidence of significant sibling correlations. The data fit a mixture of two normal distributions, especially after undergoing the Box and Cox power transformation. In each eye, the hypothesis of mendelian transmission of a major effect cannot be rejected under the tau AB free model, but is rejected under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(133 citation statements)
references
References 21 publications
(5 reference statements)
2
128
0
3
Order By: Relevance
“…The number of genes involved could not be predicted. 36 We think at present, given the locus found on chromosome 1q,16 the small number of ABCR mutations found in ARM37 and our own data, that it is hardly probable this model36 still holds.…”
Section: Segregation Analysismentioning
confidence: 86%
“…The number of genes involved could not be predicted. 36 We think at present, given the locus found on chromosome 1q,16 the small number of ABCR mutations found in ARM37 and our own data, that it is hardly probable this model36 still holds.…”
Section: Segregation Analysismentioning
confidence: 86%
“…Overview AMD is often regarded as a group of complex, late onset diseases modulated by the convergence of multiple risk factors (196,197). Family history is a consistent risk factor identified in most epidemiological studies of AMD conducted to date, and familial aggregation studies have shown that a genetic contribution is readily identified in up to 25% of AMD cases (198).…”
Section: Molecular Genetics Of Amd and Disease Associationsmentioning
confidence: 99%
“…It has been postulated that cataract and ARM might occur frequently together because of shared genetic 25,26 or environmental factors, cohort including age, diet, 27,28 light exposure 29,30 and cigarette smoking. [31][32][33][34][35][36] Current available evidence, however, is weak and inconsistent 11,12,14,15 in support of an association between cataract and ARM.…”
Section: Discussionmentioning
confidence: 99%